Trend and Geographic Variation in Incidence and Prevalence of Inflammatory Bowel Disease in Regions Across China: A Nationwide Employee Study Between 2013 and 2016 - Yang, Hong; Zhou, Runing; Bai, Xiaoyin; Guo, Mingyue; Ruan, Gechong; Wang, Li; Qian, Jiaming (Frontiers in Medicine, 2022)
Background: Incidence and prevalence rates and trends of inflammatory bowel disease (IBD) in China remain largely unknown. Objective: To estimate the nationwide prevalence and incidence of IBD and identify its noticeable trends in China between 2013 and 2016. Methods: We conducted a population-based analysis using data from the National Urban Employee Basic Medical Insurance database. Patients with at least three claims of IBD diagnosis were identified. A Joinpoint regression model was used to analyze the annual percent change (APC) of the age-standardized incidence and prevalence. Results: The age-standardized prevalence of CD increased from 1.59/100,000 in 2013 to 3.39/100,000 (p<0.05) in 2016, and that of UC increased from 8.72/100,000 to 17.24/100,000 (p<0.05) during the period, with an UC/CD ratio of 5.09 in 2016. The age-standardized incidence of CD varied between 0.82/100,000 and 0.97/100,000 (p=0.9), whereas that of UC slightly increased from 4.54/100,000 to 4.85/100,000 (p=0.7). The eastern region of China had the highest incidence and prevalence and the western region had the lowest rates, in both UC and CD, showing an east-to-west gradient. Conclusion: The incidence and prevalence of IBD in most urban regions in China had emerging trend over the study period and an east-to-west gradient was observed, which indicated a greater burden of in eastern China. Efforts to improve prevention strategies and promote awareness of IBD are needed, particularly in young men who are at higher risk for CD.